Adipose-Derived Mesenchymal Stem Cells from Ventral Hernia Repair Patients Demonstrate Decreased Vasculogenesis. (17th March 2014) - Lisiecki, Jeffrey; Rinkinen, Jacob; Eboda, Oluwatobi; Peterson, Jonathan; De La Rosa, Sara; Agarwal, Shailesh; Dimick, Justin; Varban, Oliver A.; Cederna, Paul S.; Wang, Stewart C.; Levi, Benjamin
Abstract : Introduction. In adipose tissue healing, angiogenesis is stimulated by adipose-derived stromal stem cells (ASCs). Ventral hernia repair (VHR) patients are at high risk for wound infections. We hypothesize that ASCs from VHR patients are less vasculogenic than ASCs from healthy controls. Methods. ASCs were harvested from the subcutaneous fat of patients undergoing VHR by the component separation technique and from matched abdominoplasty patients. RNA and protein were harvested on culture days 0 and 3. Both groups of ASCs were subjected to hypoxic conditions for 12 and 24 hours. RNA was analyzed using qRT-PCR, and protein was used for western blotting. ASCs were also grown in Matrigel under hypoxic conditions and assayed for tubule formation after 24 hours. Results. Hernia patient ASCs demonstrated decreased levels of VEGF-A protein and vasculogenic RNA at 3 days of growth in differentiation media. There were also decreases in VEGF-A protein and vasculogenic RNA after growth in hypoxic conditions compared to control ASCs. After 24 hours in hypoxia, VHR ASCs formed fewer tubules in Matrigel than in control patient ASCs. Conclusion. ASCs derived from VHR patients appear to express fewer vasculogenic markers and form fewer tubules in Matrigel than ASCs from abdominoplasty patients, suggesting decreased vasculogenic activity.